The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1002/app.13563
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking structures of gelatin hydrogels crosslinked with genipin or a water‐soluble carbodiimide

Abstract: It was suggested in our previous studies that carbodiimide-and genipin-crosslinked gelatin hydrogels could be used as bioadhesives to overcome the cytotoxicity problem associated with formaldehyde-crosslinked gelatin hydrogels. In this study, we investigated the crosslinking structures of carbodiimide-and genipin-crosslinked gelatin hydrogels. We found that crosslinking gelatin hydrogels with carbodiimide or genipin could produce distinct crosslinking structures because of the differences in their crosslinking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
121
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(126 citation statements)
references
References 37 publications
(54 reference statements)
2
121
0
2
Order By: Relevance
“…The cross-linking process in films generally increases the TS and decreases the percentage of elongation. However, the opposite behavior observed in our case for the GG/EDC system is in agreement with results reported for other polysaccharide and protein systems [23,45] . The EDC interacts with hydroxyl groups from the backbone or from the galactose side group, blocking the hydrogen bonding sites on the guar gum and consequently reducing the intermolecular interactions between the polymer molecules.…”
Section: Mechanical Propertiessupporting
confidence: 93%
See 1 more Smart Citation
“…The cross-linking process in films generally increases the TS and decreases the percentage of elongation. However, the opposite behavior observed in our case for the GG/EDC system is in agreement with results reported for other polysaccharide and protein systems [23,45] . The EDC interacts with hydroxyl groups from the backbone or from the galactose side group, blocking the hydrogen bonding sites on the guar gum and consequently reducing the intermolecular interactions between the polymer molecules.…”
Section: Mechanical Propertiessupporting
confidence: 93%
“…Carbodiimides have been used, for example, to cross-link blends of collagen and polyvinyl alcohol and shown to be more efficient in the release of a growth hormone than the same system cross-linked with glutaraldehyde [22] . Liang et al [23] studied hydrogels of gelatin cross-linked with EDC and genipin lattices. The authors observed that carbodiimides can form intra-and intermolecular bonds in gelatin.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous reaction of genipin as azaphilone with an amino group forms a nitrogen-iridoid which undergoes dehydration to form an aromatic monomer [45] . Others speculate that genipin molecules may be polymerized before crosslinking with amino groups [31] .…”
Section: Crosslinking Of Gelatin Microspheresmentioning
confidence: 99%
“…Genipin is a naturally occurring crosslinker obtained from the fruits of Gardenia jasminoides. It has been gaining importance in biomedical industries due to its far less cytotoxic nature as compared with glutaraldehyde (10,11).…”
Section: Introductionmentioning
confidence: 99%